Low carbon performance evaluation of China's power industry driven by artificial intelligence—Take Shanghai Electric Power Co., Ltd. as an example - Anyuan Zhang (Heliyon)
Currently, China is vigorously promoting the transformation of industrial enterprises' manufacturing, and low-carbon development has become an important research direction in the transformation, especially in the energy industry. For China's electric power enterprises, it is urgent to create a performance evaluation system and method suitable for the characteristics of this industry. This paper uses the DPSIR-TOPSIS model to simplify the complexity of the overall problem, and fully considers the impact of the overall environment to establish an indicator system and framework. Taking Shanghai Electric Power Co., Ltd. as an example under the background of impact of AI on low-carbon production as an example. Through the DPSIR-TOPSIS analysis driven by AI, the enterprise should have a clearer planning and understanding of the future strategy. On this basis, according to result of evaluation, combining with analysis of each yearly work done by the company, suggestions like companies need to keep informed of their state and respond,and to encourage relevant research, and form special support funds or support policies were given to improve the further low carbon work of China's power industry.